AREAL AND PRODUCTION OF PALM OIL TREES - Setiowati, Yuli; Jufri, Fikri; Arahman; Asman; Huda, Ismul (MSJ : Majority Science Journal, 2024)
Palm oil is one of the plantation products that has a significant impact on the Indonesian economy. Indonesia, being one of the major palm oil exporters in the world, has successfully reduced poverty and unemployment rates by expanding oil palm plantation areas. This research aims to explore the relationship between the extent of oil palm plantation land and the annual production of palm oil in Paser Regency. The research method employed for this study is quantitative, involving the collection of data on the amount of palm oil plantation land from 2018 to 2022, along with the annual palm oil production figures in Paser Regency. The gathered data will be examined using correlation analysis, utilizing IBM SPSS 25 as the tool for conducting the correlation analysis. The researcher found that there is no significant correlation between the extent of oil palm plantation land and annual palm oil production. Additionally, the researcher discovered other variables that correlate with the annual volume of palm oil production, which were not considered in this study. The variables identified by the researcher as influencing production volume after conducting this study include soil conditions, fertilizers, seedlings, human resources, and the age of oil palm trees. This research provides insights to readers, stakeholders, and other researchers regarding factors correlated with the annual volume of palm oil production. These findings can serve as a solid foundation for business decision-making and as reference material for future research.